Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s40064-016-2721-4
|View full text |Cite
|
Sign up to set email alerts
|

Headache in Behcet’s disease: types and characteristics

Abstract: BackgroundBehcet’s disease involves several systems in the body. Neurological involvement is identified by different symptoms. Headache is one of the common complaints of patients with Behcet’s disease. It might be a part of neurological involvement or may arise independently in the course of disease. Studies with small sample size have resulted in various findings in this field. Since the prevalence of Behcet’s disease is relatively high in Iran, this study was carried out to compare the features of headache … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Headache has been reported to be the most common neurological symptom of BD 232425. Consistently, headache was observed in nearly half of the present patients with NBD and those with BD without neurological involvement.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Headache has been reported to be the most common neurological symptom of BD 232425. Consistently, headache was observed in nearly half of the present patients with NBD and those with BD without neurological involvement.…”
Section: Discussionsupporting
confidence: 81%
“…Although headache can present as a sign of NBD, it also frequently occurs independently in patients with BD. Previous studies of the occurrence of headache in patients with BD found that tension-type headache and migraine are common,232425 as they are in the general population. Both the present and previous studies found that only 10% of the headache in patients with BD is due to NBD 2627.…”
Section: Discussionmentioning
confidence: 95%
“…Up to 82% of patients may have some form of headache. 129 Migraine and tension-type headaches are reported to be most frequent. Headaches can occur in the setting of true neurologic involvement, as described earlier, or for other reasons, including hypertension.…”
Section: Immunoglobulin G4-related Diseasementioning
confidence: 99%
“…They last for a short period and very severe headaches and have various episodes a day. The pain and the independent symptoms result from the activation of the trigeminal nerve and the parasympathetic nervous system due to the facialtrigeminal reflex in the brainstem or the pathological activation (Moghaddassi et al, 2016). The hypothalamus is the brain region that acts as a producer that enhances such reflex.…”
Section: Trigeminal Autonomic Cephalalgiamentioning
confidence: 99%
“…It is usually vibrant such as heartbeats and might be associated with vomiting, nausea, and a discomfort that becomes worse with noise (phonophobia), smells (osmophobia), and light (photophobia), (Matar et al, 2015). The pain becomes worse with physical activity, enhances with rest, and might be caused by stress periods, climate changes, menstruation, fasting, some foods, hunger, or changes in sleep pattern (sleepless, or even more than usual) (Moghaddassi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%